GOVERNANCE AND FOREIGN DIRECT INVESTMENT AN ECONOMETRIC STUDY OF PAKISTAN: A COMPARISON WITH SOUTH ASIAN COUNTRIES (Pakistan Business Review, 2021)
This paper makes analysis on governance link with foreign direct investment and debates on the comparison with some South Asian economies. The paid data of composite governance index by International Country Risk Guide from 1984-2015 has been used to estimate the results of the model. The Auto Regressive Distributive Lag (ARDL) method was proposed. The Bound test, Error correction Mechanism and structural stability tests are applied which revealed the governance indicators effectively to boost up FDI inflow. The study exposed positive empirical impact of governance on FDI in case of Pakistan.